Pragmatic Randomized Controlled Trial of Pharmacopuncture Therapy for Cervical Disc Herniation: A Pilot Study - Lee SW; Ahn YJ; Kim S; Lee Y; Cho HW; Hong Y; Nam D; Park YC; Kim EJ; Lee YJ; Ha IH (Journal of Pain Research, 2025)
Su Won Lee,1 Yong-Jun Ahn,2 Suna Kim,3 Yeonsun Lee,4 Hyun-Woo Cho,5 Yejin Hong,6 Dongwoo Nam,7 Yeon-Cheol Park,7 Eun-Jung Kim,8 Yoon Jae Lee,1 In-Hyuk Ha1 1Jaseng Spine & Joint Research Institute, Jaseng Medical Foundation, Seoul, Republic of Korea; 2Jaseng Clinical Research Center, Jaseng Hospital of Korean Medicine, Seoul, Republic of Korea; 3Jaseng Clinical Research Center, Daejeon Jaseng Hospital of Korean Medicine, Daejeon, Republic of Korea; 4Jaseng Clinical Research Center, Bucheon Jaseng Hospital of Korean Medicine, Bucheon, Republic of Korea; 5Jaseng Clinical Research Center, Haeundae Jaseng Hospital of Korean Medicine, Busan, Republic of Korea; 6Department of Acupuncture and Moxibustion, Kyung Hee University Korean Medicine Hospital, Seoul, Republic of Korea; 7Department of Acupuncture & Moxibustion, College of Korean Medicine, Kyung Hee University, Seoul, Republic of Korea; 8Department of Acupuncture & Moxibustion, College of Korean Medicine, Dongguk University Bundang Oriental Hospital, Seongnam, Republic of KoreaCorrespondence: In-Hyuk Ha, Jaseng Spine & Joint Research Institute, Jaseng Medical Foundation, 540, Gangnamdae-ro, Gangnam-gu, Seoul, 06110, Republic of Korea, Tel +82-2-2222-2740, Email hanihata@gmail.comPurpose: Cervical disc herniation (CDH) is increasingly prevalent, highlighting the need for more effective treatments. Although pharmacopuncture therapy is one of the most widely used treatment methods for CDH in Korean medicine clinical practice, there are few high-quality studies conducted in Korea. Therefore, we aimed to evaluate the efficacy and safety of pharmacopuncture therapy for CDH through a pragmatic clinical trial that reflects clinical practice while utilizing well-designed study settings of a randomized controlled trial.Patients and Methods: This three-armed, pragmatic, pilot, randomized controlled trial included pharmacopuncture (Phm-Acu), acupuncture (Acu), and usual care (UC) groups in a 1:1:1 ratio. Participants were treated twice a week for 6 weeks, with follow-up extending to week 25. The primary outcome was the neck pain Numeric Rating Scale (NRS). The secondary outcomes were arm pain NRS, neck and arm pain Visual Analog Scale, Neck Disability Index (NDI), Northwick Park Questionnaire (NPQ), Patient Global Impression of Change (PGIC), Short Form-12 Health Survey (SF-12), and EuroQol-5-dimension-5-level (EQ-5D-5L).Results: Eighty participants (Phm-Acu: 29, Acu: 29, and UC: 26) were selected. At week 7, neck pain NRS significantly decreased in the Phm-Acu group than that in the UC (2.73, 95% confidence interval (CI) 1.87– 3.59) and Acu groups (1.68, 95% CI 0.84– 2.53). Survival analysis revealed that the Phm-Acu group showed the fastest recovery rate. The Phm-Acu group showed significant improvement compared with the Acu and UC groups for all other pain outcomes and PGIC and compared with the UC group for NDI, NPQ, EQ-5D-5L, and SF-12 [physical]. The area under the curve analysis showed that the Phm-Acu group showed significant differences in all outcomes except SF-12 [mental] compared with the UC group. No serious adverse events occurred; four patients experienced mild adverse events.Conclusion: In CDH, pharmacopuncture was more effective in reducing pain and achieving functional recovery than acupuncture and usual care.Keywords: neck pain, non-invasive therapy, pain management, functional recovery